PENGARUH PERPUTARAN MODAL KERJA DAN LIKUIDITAS TERHADAP PROFITABILITAS PT. TELEKOMUNIKASI INDONESIA TBK. PERIODE 2010-2017 - Normasitoh, Kusnia; Sholihin, Ustadus; Afrianto, Dadang; Rokhman, Zaenur (FKDP (Forum Komunikasi Dosen Peneliti), 2024)
This study aims to determine the effect of working capital and liquidity turnover on profitability at PT. Telekomunikasi Indonesia Tbk. Period 2010-2017. The data used is secondary data. Data collection uses documentation and literature study techniques. The sampling technique uses purposive sampling method. The population in this study are all financial statements issued by PT. Telekomunikasi Indonesia Tbk. in the period 2010-2017, the data were 32 quarterly period observations. Data analysis techniques using multiple regression tests, coefficient of determination and hypothesis testing consisting of t test and F test. The results of this study obtained a regression equation ROA = 4,309 - 5,770 WCT + 17,038 CR. Partially the results of working capital turnover have a negative effect that has a significant effect on profitability, while liquidity has a positive effect on profitability. Working capital turnover (X1) and liquidity (X2) together have a positive and significant effect on profitability at PT. Telekomunikasi Indonesia, Tbk. Period 2010-2017.